Chemoprophylactic Assessment of Combined Intranasal SARS-CoV-2 Polymerase and Exonuclease Inhibition in Syrian Golden Hamsters - Eduardo Gallardo-Toledo; Megan Neary; Joanne Sharp; Joanne Herriott; Edyta Kijak; Chloe Bramwell; Paul Curley; Usman Arshad; Henry Pertinez; Rajith K. R. Rajoli; Anthony Valentijn; Helen Cox; et al. (Viruses, 2023)
Pibrentasvir (PIB) has been demonstrated to block exonuclease activity of the SARS-CoV-2 polymerase, protecting favipiravir (FVP) and remdesivir (RDV) from post-incorporation excision and eliciting antiviral synergy in vitro. The present study investigated the chemoprophylactic efficacy of PIB, FVP, RDV, FVP with PIB, or RDV with PIB dosed intranasally twice a day, using a Syrian golden hamster contact transmission model. Compared to the saline control, viral RNA levels were significantly lower in throat swabs in FVP (day 7), RDV (day 3, 5, 7), and RDV+PIB (day 3, 5) treatment groups. Similarly, findings were evident for nasal turbinate after PIB and RDV treatment, and lungs after PIB, FVP, and FVP+PIB treatment at day 7. Lung viral RNA levels after RDV and RDV+PIB treatment were only detectable in two animals per group, but the overall difference was not statistically significant. In situ examination of the lungs confirmed SARS-CoV-2 infection in all animals, except for one in each of the RDV and RDV+PIB treatment groups, which tested negative in all virus detection approaches. Overall, prevention of transmission was observed in most animals treated with RDV, while other agents reduced the viral load following contact transmission. No benefit of combining FVP or RDV with PIB was observed.